THE MEANING OF "TURAJAJI" FOR THE ROGA TRADITIONAL COMMUNITY NDONA TIMU DISTRICT, ENDE DISTRICT - Kusi, Josef (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2023)
The problem raised in this research is what is the meaning of Turajaji (eternal covenant) for the Roga indigenous community, East Ndona District, Ende Regency, what is the influence of Turajaji (eternal covenant) for the Roga indigenous community, East Ndona District, Ende Regency. The aim of this research is to find out the meaning of Turajaji (eternal covenant) for the Roga indigenous community, East Ndona District, Ende Regency and to determine the influence of Turajaji (eternal covenant) for the Roga indigenous community, East Ndona District, Ende Regency. The method used in this research is a qualitative research method with data collection techniques, namely observation, interviews and documentation. Meanwhile, data analysis techniques include data reduction, data presentation and drawing conclusions. The research results show that Turajaji (an eternal agreement between two or three traditional villages of different/same descent) with the aim of establishing friendship, brotherhood fosters a sense of kinship that lasts throughout life. The meaning contained in Turajaji (eternal covenant) is cultural, social, ethical meaning. The effect or consequence if one of the parties breaks the Turajaji (eternal agreement) is that they receive a mission, nature will punish, because the Turajaji has been strengthened by a deductive oath, namely the destruction of the party who violates the agreement.